Effect of solvent evaporation strategies on regional bond strength of one‐step self‐etch adhesives to root canal dentine. (22nd March 2013) - Thitthaweerat, S.; Nakajima, M.; Foxton, R. M.; Tagami, J.
Abstract: Aim: To evaluate the efficacy of different solvent evaporation strategies on bonding of one‐step self‐etch adhesives to root canal dentine. Methodology: Two dual‐cure resin core systems (Clearfil DC Bond/Clearfil DC Core Automix and Clearfil Tri‐S Bond Plus/Clearfil DC Core Plus; Kuraray Noritake Dental, Tokyo, Japan) were equally applied in 24 post spaces from extracted human mandibular premolars. After the adhesive application, specimens were randomly assigned into four water/solvent evaporation strategies as follows (I) insertion of absorbent paper point for 10 s: P, (II) 10 s air‐blowing: A, (III) as (II) followed by insertion of absorbent paper point: AP, (IV) as (III) followed by 10 s additional air‐blowing: APA . Then, the adhesives were light cured, and resin core materials were placed into the post space, followed by light curing for 60 s. After water storage for 24 h, 0.6 × 0.6 mm‐thick beams were prepared to measure the regional μTBS. The mode of failure was also observed. The μTBS values were statistically analysed using three‐way anova and Duncan HSD test ( α =  0.05). Results: In the coronal region, there were no significant differences in μTBS between each evaporation strategy ( P  >   0.05), except P group. However, in the apical region, APA and AP groups significantly increased in μTBS compared with A and P groups ( P  <   0.05). Only in the APA group of Clearfil Tri‐S Bond Plus/Clearfil DC Core Plus, was there no significant difference in μTBS between the coronal and apical regions ( P  >   0.05). Conclusion: The use of paper points with additional air‐blowing for removing excessive adhesive and evaporating residual water/solvent would be effective in producing higher bond strength for the tested one‐step self‐etch adhesives and fewer blister formations in deeper regions of the post space.